(untitled) (Research, Society and Development, 2020)
Futsal is one of the most practiced sports in Brazil, having as main competition the National Futsal League, which over the years has been acquiring a lot of space in the national sports scene and with considerable media coverage. In view of this growth, there are numerous studies on the modality of futsal, but there is a scarcity of research on the aspects of sports management of clubs participating in the country’s league. Therefore, this study aimed to conduct a survey and analyze the geographic and sponsorship profile of the teams participating in the National Futsal League between the years 2016-2019. The focus of the research was on the identification of the region where the teams are installed, regarding the states and the size of the cities, as well as the characterization of the sponsoring brands. For this, a qualitative research of a descriptive nature was carried out, having as main source of data the documentary analysis. Data were collected from official platforms, team websites and official team profiles on social networks. The results show that despite being a national championship, most teams are located in the south and southeast regions, while the Northeast and Midwest regions did not participate in the league during the years analyzed. As for the sponsors, it can be noted that the teams receive sponsorship from companies that are located in the region of the teams, given the local visibility with modality.